Inhibitory Effects of Isoliquiritigenin and Licorice Extract on Voltage-Dependent K+ Currents in H9c2 Cells - Chisato Noguchi; Jing Yang; Kazuho Sakamoto; Ryo Maeda; Kenji Takahashi; Hiroshi Takasugi; Tomoyuki Ono; Masahiro Murakawa; Junko Kimura (Elsevier, 2008)
The effect of isoliquiritigenin (ISL), a component of licorice, on the voltage-dependent, ultra-rapidly activating delayed-rectifier K+ current (IKur) was examined in H9c2 cells, a cell-line derived from rat cardiac myoblasts. IKur was recorded using the whole-cell patch clamp method with a pipette solution containing 140 mM K+. Depolarizing voltage pulses of 200-ms duration were given with 10-mV steps every 10 s from − 40 mV holding potential. ISL inhibited IKur in a concentration-dependent manner. The median inhibitory concentration (IC50) of ISL was approximately 0.11 μM and the Hill coefficient was 0.71. Using CHO cells expressing Kv1.5 IKur channels, ISL also inhibited Kv1.5 IKur, but less potently than the IKur current in H9c2 cells. Furthermore, in H9c2 cells, the licorice extract itself inhibited IKur in a manner similar to ISL. We conclude that ISL, one component of licorice, is a potent inhibitor of K+ channels, which specifically in H9c2 cells could be Kv2.1, and that this inhibition may be involved in various pharmacological effects of licorice. Keywords:: isoliquiritigenin, ultra-rapidly activating delayed-rectifier K+ current, H9c, 2 cell, Kv2.1, Kv1.5